'Twas the night before Christmas - Moore, Clement Clarke 1779-1863; Marshall, Mark 1969- (Wilton, CT Tiger Tales, 2015)
'Twas the night before Christmas, when all through the house, not a creature was stirring, not even a mouse. It's Christmas Eve, and the entire house is sleeping -- except one boy, woken by the clatter of hooves on the roof. As he tiptoes downstairs, who will he find?
105037
Keywords: Santa Claus -- Juvenile poetry; Children's poetry, American; Narrative poetry; American poetry; Santa Claus; Christmas -- Poetry; Juvenile works; Poetry